2010
DOI: 10.1002/jor.21175
|View full text |Cite
|
Sign up to set email alerts
|

Temporal tissue patterns in bone healing of sheep

Abstract: Secondary fracture healing in long bones leads to the successive formation of intricate patterns of tissues in the newly formed callus. The main aim of this work was to quantitatively describe the topology of these tissue patterns at different stages of the healing process and to generate averaged images of tissue distribution. This averaging procedure was based on stained histological sections (2, 3, 6, and 9 weeks post-operatively) of 64 sheep with a 3 mm tibial mid-shaft osteotomy, stabilized either with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…Water-like MRI lesions feature both, acute focal inflammation with microvascular hyperpermeability (in bone and in uninjured adjoining soft tissues, due to inflammatory cytokines [30]), and chronic focal hyperemia (from newly grown fibrovascular reparative tissue preceding woven bone callus) [3032]. Histopathology of active-stage Charcot foot has revealed all of these entities [33,34] as part of the physiologic secondary healing of cortical and cancellous bone fractures [27,30], and of reactive adjoining soft-tissue inflammation like tenosynovitis [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-like MRI lesions feature both, acute focal inflammation with microvascular hyperpermeability (in bone and in uninjured adjoining soft tissues, due to inflammatory cytokines [30]), and chronic focal hyperemia (from newly grown fibrovascular reparative tissue preceding woven bone callus) [3032]. Histopathology of active-stage Charcot foot has revealed all of these entities [33,34] as part of the physiologic secondary healing of cortical and cancellous bone fractures [27,30], and of reactive adjoining soft-tissue inflammation like tenosynovitis [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Unchanged or stagnant EESC on eleven FUS (in grade 1 cases) was attributed to impaired healing associated with hypertrophic fibrovascular tissue and callus, as indicated by osteosclerosis and joint fusion (ankylosis) seen on plain x-rays obtained simultaneously. Most likely, ineffective immobilization of the bone fragments was the underlying factor, causing hyperplasia of fibrous rather than of mineralized callus [32,40]. …”
Section: Discussionmentioning
confidence: 99%
“…Respective tissue compositions show typical patterns of secondary bone healing under axial compressive loading (figure 4) according to Vetter et al [51]. However, in the cases with small IFM (V1, V2, V4), large amounts of intramedullary cartilage are formed, whereas for large IFM (case V3 and V5), this cartilage formation is not visible, according to respective in vivo results [34].…”
Section: Third Step: Model Corroboration On Various Loading Conditionsmentioning
confidence: 94%
“…For both axial load cases, evaluation of the simulated change of tissue distribution over the healing time (figure 3, first two columns) revealed that according to the in vivo results of Vetter et al [51] physiological patterns can be predicted as follows. Initial intramembranous bone formation was predicted periosteally but not in the gap.…”
Section: Second Step: Model Evaluation On Tissue Distributionmentioning
confidence: 99%
See 1 more Smart Citation